A flexible wall permeameter for measurements of water and air coefficients of permeability of residual soils - Samingan, Agus Setianto (2011)
This paper describes the development of a flexible wall permeameter apparatus for measuring the water and air coefficients of permeability of residual soils. Water and air coefficients of permeability were obtained for both the drying and wetting cycles for residual soils using the flexible wall permeameter. Volume changes of the soil specimens during unsaturated consolidation and during the water and air permeability measurements were also monitored. Factors that influence the measurements, such as hydraulic and pneumatic gradients and temperature fluctuations are described and discussed in this paper. The developed flexible wall permeameter was found to be capable of measuring water and air coefficients of permeability as low as 10 12 m/s.